Danon disease is an underdiagnosed cause of advanced heart failure in young female patients: a LAMP2 flow cytometric study. (13th July 2020) - Gurka, Jiri; Piherova, Lenka; Majer, Filip; Chaloupka, Anna; Zakova, Daniela; Pelak, Ondrej; Krebsova, Alice; Peichl, Petr; Krejci, Jan; Freiberger, Tomas; Melenovsky, Vojtech; Kautzner, Josef; et al.
Abstract: Aims: Danon disease (DD) is a rare X‐linked disorder caused by mutations in the lysosomal‐associated membrane protein type 2 gene ( LAMP2 ). DD is difficult to distinguish from other causes of dilated or hypertrophic cardiomyopathy (HCM) in female patients. As DD female patients regularly progress into advanced heart failure (AHF) aged 20–40 years, their early identification is critical to improve patient survival and facilitate genetic counselling. In this study, we evaluated the prevalence of DD among female patients with non‐ischemic cardiomyopathy, who reached AHF and were younger than 40 years. Methods and results: The study cohort comprised 60 female patients: 47 (78%) heart transplant recipients, 2 (3%) patients treated with ventricular assist device, and 11 (18%) patients undergoing pre‐transplant assessment. Aetiology of the cardiomyopathy was known in 15 patients (including two DD patients). LAMP2 expression in peripheral white blood cells (WBC) was tested by flow cytometry (FC) in the remaining 45 female patients. Whole exome sequencing was used as an alternative independent testing method to FC. Five additional female DD patients (two with different novel LAMP2 mutations) were identified by FC. The total prevalence of DD in this cohort was 12%. HCM phenotype (57% vs. 9%, * P  = 0.022) and delta waves identified by electrocardiography (43% vs. 0%, ** P  = 0.002) were significantly more frequent in DD female patients. Conclusions: Danon disease is an underdiagnosed cause of AHF in young female patients. LAMP2 expression testing in peripheral WBCs by FC can be used as an effective screening/diagnostic tool to identify DD in this patient population.